THE ROLE OF MOTHER LANGUAGE IN PERSONAL SPIRITUALITY - Zilola Aliyorova Saydulla qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
This article discusses the formation of the Uzbek language, the role of the language in the spirituality of the individual, its place in society. The work pays attention to the works in order to show the artistic charm and originality of our language. The attitude to the practical work carried out in our country to increase the importance of the Uzbek language was expressed.